The Impact of Face-Face Learning after the Pandemic on the Attention and Independence of Elementary School Students - Tjandra, Camelia; Selvianita, Debby (Edunesia : Jurnal Ilmiah Pendidikan, 2023)
In recent years, the transition from online to face-to-face education has become an issue that plagues many educators and parents. As the pandemic forced schools to close and switch to distance learning, students had to adapt to new ways of learning. However, the impact of this transition on student concentration and independence is still under study. This study aims to summarize recent findings on the impact of this transition on student concentration and independence. This study aims to collect data using survey and interview methods to determine students' attention and independence. Researchers created Likert scale questionnaires and interviews. The respondent is a primary school teacher from her 1st grade to her 5th grade at Binus School Simprug Jakarta. A total of 20 teachers interviewed her 15 male teachers and her 5 female teachers. The results showed that most students tend to stay focused and be more independent when learning onsite compared to learning online. However, more research is needed to fully understand the magnitude of these effects and how they can be mitigated in an online learning environment. Overall, this summary highlights the importance of considering the influence of the learning environment on student learning outcomes and the need for further research in this area.